CHALLENGES OF TEACHING ENGLISH TO YOUNG LEARNERS IN SMALL CLASSROOM - Maulana, Rivki Surya; Fahriany, Fahriany (STKIP Persada Khatulistiwa Sintang, 2025)
This qualitative study explores the challenges faced by teachers delivering offline, small-group English courses to young learners. It has been known that it is best for students to learn English at an early age. The class size itself is relatively small compared to formal school class. These classes have around three to six students. Despite that, it has been found that the teaching process, even in the small classroom, is not without challenges. There were two experienced teachers who had participated in this study. Through interviews with teachers and classroom observations, the study identifies two key obstacles: student shyness hindering participation and frequent mood swings disrupting the learning environment. Students who are shy are not willing to participate in the activity which stalled the learning process. Also, their frequent mood-swing proves to be difficult to handle as the students could just stop participating or even be disruptive toward their friends . These findings highlight that effective instruction for young learners goes beyond just lesson planning and selecting materials. Teachers need to actively cultivate an engaging and confidence-building classroom environment. The study emphasizes the importance of utilizing positive reinforcement and ensuring all students within the small group setting receive equal attention. This understanding can inform the development of more effective teaching strategies for teachers of young learners in offline small-group English courses.Keywords: English; English Course; Small Group Classroom; Young Learners